John Kelsay and “Sharia Reasoning” in Just War in Islam: An Appreciation and a Few Propositions - Ṭībī, Bassām (A journal of church and state, 2011)
Over the past two decades, for a number of reasons, there has been a decline in the quality of scholarship on Islam in the West, be it in the United States or i